1999
DOI: 10.1101/gad.13.13.1754
|View full text |Cite
|
Sign up to set email alerts
|

The Iroquois homeodomain proteins are required to specify body wall identity in Drosophila

Abstract: The Iroquois complex (Iro-C) homeodomain proteins allow cells at the proximal part of the Drosophila imaginal wing disc to form mesothoracic body wall (notum). Cells lacking these proteins form wing hinge structures instead (tegula and axillary sclerites). Moreover, the mutant cells impose on neighboring wild-type cells more distal developmental fates, like lateral notum or wing hinge. These findings support a tergal phylogenetic origin for the most proximal part of the wing and provide evidence for a novel pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
111
0
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(118 citation statements)
references
References 41 publications
6
111
0
1
Order By: Relevance
“…This dual function is consistent with the successive roles found for Iro genes in the Drosophila wing imaginal disc Leyns et al, 1996;Grillenzoni et al, 1998;Diez del Corral et al, 1999;Calleja et al, 2002). Like its Drosophila cognate genes, iro7 is required for successive steps of the patterning of an embryonic territory.…”
Section: A Dual Role For Iro7 In the Anterior Hindbrainsupporting
confidence: 64%
“…This dual function is consistent with the successive roles found for Iro genes in the Drosophila wing imaginal disc Leyns et al, 1996;Grillenzoni et al, 1998;Diez del Corral et al, 1999;Calleja et al, 2002). Like its Drosophila cognate genes, iro7 is required for successive steps of the patterning of an embryonic territory.…”
Section: A Dual Role For Iro7 In the Anterior Hindbrainsupporting
confidence: 64%
“…290), rat antitropomyosin (Tropo, 1:1000, Abcam MAC141), and mouse anti-b-PS-integrin (1:50, Developmental Studies Hybridoma Bank). Rabbit anti-Mid (1:800) was obtained from Susumu Hirose (Liu et al 2009); mouse anti-Lb (1:3000) was obtained from Krzystof Jagla (Jagla et al 1998); rat anti-Org-1 (1:200) was obtained from Manfred Frasch (Schaub et al 2012); rabbit anti-Slouch (1:200) , rat anti-Ara, and anti-Caup (1:200) were obtained from Sonsoles Campuzano (Diez del Corral et al 1999); and anti-Stripe A (1:200) was obtained from Talila Volk (Becker et al 1997). Secondary antibodies included Alexa Fluor-conjugated antichicken, antirat, antimouse, antirabbit, and anti-guinea pig (1:200, Invitrogen).…”
Section: Immunohistochemistry and Immunofluorescencementioning
confidence: 99%
“…7,9 Now, we have shown their ability to, in addition, control the size of the territories they specify. 16 We consider this of interest in the context of current models for territorial specification.…”
Section: Integrating Cell Cycle Control By Iro Proteins In Current Momentioning
confidence: 99%
“…13 Iro genes contribute to territorial growth in the eye and wing imaginal discs by generating organizing borders at the Keywords: cell proliferation, Drosophila, imaginal discs, Iroquois genes, tumor suppressor genes List of abbreviations and acronyms: ara, araucan; CBD, Cyclin Binding Domain; Cdk2, Cyclin-dependent kinase 2; caup, caupolican; HD, homeodomain; Iro, Iroquois; Irx, Iroquois-related genes; mirr, mirror; TALE, Three Amino acid Loop Extension; TSG, Tumor Suppressor Genes confrontation of Iro-expressing and nonexpressing cells (the dorso/ventral and the notum/wing hinge organizers, respectively. [7][8][9]14 ) In addition, the observation that clones of iro mutant cells in the eye disc are larger than wild-type clones suggested that Iro proteins played a role in the control of cell proliferation. 8,15 Indeed, Iro proteins cell-autonomously restrain cell proliferation in Drosophila, both during normal development and in several established tumor-like models.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation